Preventive culture and oral health condition of patients with HIV / AIDS treated in a national hospital - Pérez Cahuaya, Lisbeth Cynthia (2013)
The aim of the study was to determine the safety culture and oral health status of patients with HIV / AIDS care in a national hospital in 2012. The type of study was descriptive, cross-sectional and retrospective. The sample consisted of 250 patients of both sexes. The sample selection was convenience. The method used for data collection was questionnaire and clinical observation. The results were: a level of oral health preventive culture low in 67.6%, moderate presence of plaque in 55.6%, moderate in 64.4% gingivitis; DMFT equal to 4.84 ± 1.96, and poor oral hygiene habits by 58%. Oral lesions presented more frequently: oral candidiasis (32.8%) and oral (3.2%) herpes. It was determined that patients with HIV / AIDS mainly presented a low level of safety culture in oral health, and regular level of oral health status.